Dynamics of spontaneous flipping of a mismatched base in DNA duplex - Yin, Yandong (National Academy of Sciences, 2014)
DNA base flipping is a fundamental theme in DNA biophysics. The dynamics for a B-DNA base to spontaneously flip out of the double helix has significant implications in various DNA–protein interactions but are still poorly understood. The spontaneous base-flipping rate obtained previously via the imino proton exchange assay is most likely the rate of base wobbling instead of flipping. Using the diffusion-decelerated fluorescence correlation spectroscopy together with molecular dynamics simulations, we show that a base of a single mismatched base pair (T–G, T–T, or T–C) in a double-stranded DNA can spontaneously flip out of the DNA duplex. The extrahelical lifetimes are on the order of 10 ms, whereas the intrahelical lifetimes range from 0.3 to 20 s depending on the stability of the base pairs. These findings provide detailed understanding on the dynamics of DNA base flipping and lay down foundation to fully understand how exactly the repair proteins search and locate the target mismatched base among a vast excess of matched DNA bases.